PENGARUH STRUKTUR MODAL, STRUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI TAHUN 2012-2015) - Ariesanti, Rida Ayu; Soegiarto, Dwi (Jurnal Bulletin, 2018)
Effect of Capital Structure, Ownership Structure, and Company Size on Company Value (Study on Property Companies listed on BEI 2012-2015). This study aimed to empirically examine the influence of capital structure, ownership structure and also firm size on firm value with control variables profitability and firm growth. Firm value proxied by price book value as a measure of firm value based on market ratio. Collecting data using a purposive sampling method for property companies listed in Indonesian Stock Exchange for the period 2012-2015. The number of sample used were 9 companies. The method of analysis of the study used multiple regression.The results find that the capital structure had positive and insignificant influence on firm value; multiple large shareholder structure had positive and insignificant influence on firm value; institutional ownership had negative and insignificant influence on firm value;Â  managerial ownership had positive and insignificant influence on firm value; while firm size had positive and significant influence on firm value